Miscellaneous bean viruses - Gálvez E., Guillermo E.; Castaño, M.J. (International Center for Tropical Agriculture, 1980)
Bean crops are attacked by several viruses transmitted by insects among which are: (1) the alfalfa mosaic virus (aphids); susceptibility is correlated with plant age; (2) curly top (Circulifer tenellus); the best control measure is the utitilization of resistant var.; (3) bean summer death (Orosius argentatus); (4) tomato spotted wilt virus, which is transmitted mechanically and by various types of thrips; (5) red node, which is transmitted mechanically and in the seed. Insect vectors have not been reported; it can be controlled using resistant var. (CIAT)